Dampak Fintech Terhadap Masa depan Perbankan Konvensional dalam Konteks Bank Mandiri - Ocid Rosadi (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
The emergence of financial technology (fintech) has brought significant disruption to the conventional banking industry. Fintech offers faster, cheaper and more accessible financial services, which appeal to many customers, especially the younger generation. This study aims to analyse the impact of fintech on the future of conventional banking, with a focus on Bank Mandiri, one of the largest banks in Indonesia. The results show that fintech has a significant impact on various aspects of conventional banking, including: 1) Products and services. Fintech offers innovative and diverse financial products and services that conventional banks cannot access. 2) Distribution channels: Fintechs utilise digital technology to reach customers directly, without the need for physical branches. 3) Business model. Fintech has a more efficient and cost-effective business model compared to conventional banks. 4) Customer engagement. Fintech offers a more personalised and interactive customer experience. Bank Mandiri shows that the bank has taken various strategic steps to face competition with fintech, such as: developing digital services, collaborating with fintech startups, improving operational efficiency. Disputes between fintech consumers and fintech service providers can be resolved through: negotiation, mediation, arbitration, court and legal comparison with default. In addition, we also highlight the need for collaboration between government agencies, industry players, and the tech community to develop a comprehensive and adaptive regulatory framework.